Trends in potentially avoidable hospitalizations for diabetes in Switzerland, 1998 to 2018: Data from multiple cross-sectional studies - Ko Ko Maung; Charlène Mauron; Alexandre Gouveia; Pedro Marques-Vidal (Heliyon)
Background: Timely and appropriate outpatient care can prevent potentially avoidable hospitalizations (PAH) for diabetes. We analysed the trends, determinants, and consequences of PAH for diabetes in Switzerland over two decades. Methods: hospital discharge data for years 1998–2018 were used. PAH were defined according to the Organization for Economic Cooperation and Development criteria. Results: Overall, 90,853 admissions were considered as PAH, of which 25,376 (27.8 %), 9789 (10.8 %) and 55,688 (61.4 %) represented uncontrolled diabetes, short-term and long-term complications, respectively. The number of PAH increased from 2600 in 1998 to 5730 in 2018, mostly due to long-term complications. Compared to PAH for long-term complications, admissions for uncontrolled diabetes and short-term complications were more frequently women, in the younger age categories, more frequently non-Swiss, without health insurance, were more frequently admitted in an emergency setting, at the patient's initiative or via emergency services (ambulance, police), and had a lower comorbidity index. PAH for uncontrolled diabetes and short-term diabetic complications were more frequent in the non-German speaking regions. Patients with PAH for short-term diabetic complications were more frequently admitted to the intensive care unit, and their length of stay was shorter. In 2018, PAH for diabetes represented 56,255 days, corresponding to 155 hospital beds occupied yearly, and an estimated cost of 76 million CHF. Conclusion: In Switzerland, the number PAH for diabetes increased during the period 1998–2018. PAH types differ according to geographic region and to the patient's characteristics, and a sizable fraction is related to uncontrolled diabetes or likely preventable short-term complications.